97.0k views
1 vote
Can someone please help me with this problem? problem attached. Thank you​

Can someone please help me with this problem? problem attached. Thank you​-example-1
User Xlm
by
5.1k points

2 Answers

2 votes
I thin the answer is A
User Gulli Meel
by
4.1k points
3 votes

Answer:

The expression simplifies to:

=
(\tan\theta)/(\sin ^2 \theta+\cos ^2 \theta)=\tan\theta}

Explanation:

Given trigonometric expression:


(\tan\theta)/(\sin ^2 \theta+\cos ^2 \theta)

Using identity :


\sin ^2 \theta+\cos ^2 \theta=1


(\tan\theta)/(\sin ^2 \theta+\cos ^2 \theta)


=(\tan\theta)/(1)

The expression simplifies to:

=
(\tan\theta)/(\sin ^2 \theta+\cos ^2 \theta)=\tan\theta}

User Ali Hosseini
by
4.9k points